GEOMORFOLOGI TEKTONIK DAERAH ALIRAN SUNGAI CIWIDEY DAN CISANGKUY DI CEKUNGAN BANDUNG - Nendi rohaendi; Emi Sukiyah; Dicky Muslim; Athanasius Cipta (PPSDM Geominerba, 2021)
Bandung urban area is located in the intra-mountain basin which is part of upstream Citarum watersheds. The aim of the research is to analyse tectonic geomorphology of sub-watershed Ciwidey and Cisangkuy in the southern part of Bandung basin. The method use digital elevation image from DEMNAS combined with geological data. The result shows that the southern part of Bandung basin is tectonically active. This information is significant to evaluate existing spatial planning based on natural hazard point of views.